Fault Recovery and Redundancy in Real-time Wireless TDMA - WEBER, STEFAN; GLEESON, MARK (My University, 2008)
This paper aims to address the issue of message delivery reliability in real-time, wireless communication systems. We discuss the provision of a probabilistic admissions control protocol that adapts retransmissions of frames to reflect the reliability of the medium and the required timeliness of real-time data for transmission. We utilise a two-pronged approach: firstly, admissions control to ensure transmission time is reserved such that retransmissions are possible, and secondly, an exponential backoff process to reschedule failed transmissions on a station-by-station basis. Combining these measures, we ensure the fulfillment of real-time guarantees while tolerating a limited loss of frames on the medium.
PUBLISHED
Keywords: Computer Science